Population genetic and phytochemical dataset of Saraca asoca: a traditionally important medicinal tree - Hegde, Satisha; Pai, Sandeep Ramchandra; Bhagwat, Rasika M.; Sainia, Archana; Rathore, Poonam Kanwar; Jalalpure, Sunil Satyappa; Hegde, Harsha Vasudev; Sugunan, Attayoor Purushottaman; Gupta, Vidya S.; Kholkute, Sanjiva D.; Roy, Subarna (Data in Brief, 2019)
The data presented in this article is in support of the research paper “Genetic and phytochemical investigations for understanding population variability of the medicinally important tree Saraca asoca to help develop conservation strategies” Hegde et al., 2018. This article provides PCR based Inter-Simple Sequence Repeat (ISSR) and HPLC datasets of 106 individual samples of Saraca asoca collected from various geographical ranges of the Western Ghats of India. The ISSR data includes information on genetic diversity and images of population structures generated through amplified DNA products from samples of Saraca asoca leaf. Phytochemical data obtained from HPLC includes concentration (mg/g) of gallic acid (GA), catechin (CAT), and epicatechin (EPI). The data also presents information obtained from various statistical analysis viz. standard error of the mean values, distribution variables, prediction accuracy, and multiple logistic regression analysis.